An efficient fiber-based ELISA for detection of antibody against fowl adenovirus serotypes 7 and 8. (May 2020) - Lu, Hao; Wang, Weikang; Zhang, Jianjun; Shao, Hongxia; Li, Luyuan; Li, Tuofan; Xie, Quan; Wan, Zhimin; Qin, Aijian; Ye, Jianqiang
An outbreak of inclusion body hepatitis caused by fowl adenovirus serotype 8 (FAdV-8) has caused significant economic losses in the poultry industry worldwide. However, a rapid serology test kit specific to FAdV-8 is not available to date. We developed a fiber-based ELISA using the purified GST-fiber of FAdV-8 as coating antigen to measure antibodies against FAdV-8. Specificity analysis showed that our ELISA could react with sera against FAdV-7, -8a, and -8b, but not with sera against the other pathogens tested. Moreover, detection of positive sera with our ELISA had 83% and 94% agreement with an indirect immunofluorescence assay (IFA) and a commercial ELISA from BioChek, respectively. Our ELISA was also effective in the detection of antibodies against FAdV-8 in sera from both experimentally infected and clinically vaccinated chickens. Our FAdV-8 fiber-based ELISA can be a valuable tool to specifically and sensitively detect antibodies against FAdV-7 and/or -8 in infected or vaccinated chickens.